Pendidikan Moderasi Beragama:Membangun Toleransi Dan Keberagaman - Dhea Gita Ananda; Aisyah Puspita; Dewi Lidia (AL-Ikhtiar : Jurnal Studi Islam, 2024)
This article reviews the importance of religious moderation, tolerance and diversity in social and religious contexts. Religious moderation refers to a balanced approach to practicing religious teachings, while religious tolerance includes respect for differences in religious beliefs and practices between individuals and groups. Diversity, on the other hand, includes various dimensions such as religion, culture and ethnicity that enrich the social and cultural life of society.The importance of religious moderation, tolerance and diversity is reflected in their role in building social harmony and preventing interreligious conflict. These principles also form the basis for peaceful coexistence and respect for human rights in practicing their beliefs. Implementation of religious moderation involves education in the values of tolerance from an early age, promotion of interfaith dialogue, and inclusive public policies to support diversity. The benefits include creating an inclusive social environment, strengthening peace in multicultural societies, and developing open-minded individuals who contribute positively to building diverse and harmonious communities. Thus, this article emphasizes the importance of religious moderation, tolerance and diversity as the foundation for a just, co-existent and sustainable society. Abstrak Artikel ini mengulas pentingnya moderasi beragama, toleransi, dan keberagaman dalam konteks sosial dan keagamaan. Moderasi beragama mengacu pada pendekatan yang seimbang dalam menjalankan ajaran agama, sementara toleransi beragama mencakup penghargaan terhadap perbedaan keyakinan dan praktik keagamaan antarindividu dan kelompok. Keberagaman, di sisi lain, mencakup berbagai dimensi seperti agama, budaya, dan suku bangsa yang memperkaya kehidupan sosial dan budaya masyarakat.Pentingnya moderasi beragama, toleransi, dan keberagaman tercermin dalam peran mereka dalam membangun harmoni sosial dan mencegah konflik antaragama. Prinsip-prinsip ini juga membentuk dasar bagi kehidupan bersama yang damai dan menghormati hak asasi manusia dalam menjalankan keyakinan mereka. Implementasi moderasi beragama melibatkan pendidikan nilai-nilai toleransi sejak dini, promosi dialog antaragama, serta kebijakan publik yang inklusif untuk mendukung keberagaman. Manfaatnya termasuk menciptakan lingkungan sosial yang inklusif, memperkuat kedamaian dalam masyarakat multikultural, dan mengembangkan individu yang berpikiran terbuka serta berkontribusi positif dalam membangun komunitas yang beragam dan harmonis. Dengan demikian, artikel ini menekankan pentingnya moderasi beragama, toleransi, dan keberagaman sebagai fondasi bagi masyarakat yang adil, berdampingan, dan berkelanjutan.